2012
DOI: 10.1590/s0100-69162012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Operational parameters of soybean seeding in santa fe system

Abstract: The use of no tillage system associated with the crop-livestock integration is an alternate managing that promotes the accumulation of dry matter in the soil, an essential fact to make the system sustainable and profitable. The aim of this study was to evaluate the operational performance of a planter-tractor set on maize straws intercropped with Urochloa, in different seeding modes. The soybean crop was seed on the intercropping of two forage species (Urochloa brizantha and Urochloa ruziziensis) in five cropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Chioderoli et al (2012) observed the effect of different systems of intercropping with brachiaria on these variables, attributed to the quantity of straw.…”
Section: Res Ults and Discussionmentioning
confidence: 98%
“…Chioderoli et al (2012) observed the effect of different systems of intercropping with brachiaria on these variables, attributed to the quantity of straw.…”
Section: Res Ults and Discussionmentioning
confidence: 98%